Weight loss and diet changes in obese patients receiving low-frequency transcutaneous vagal nerve stimulation: results of a randomized placebo-controlled study - E. A. Rogozhkina; N. S. Karamnova; O. B. Shvabskaya; O. N. Dzhioeva; O. M. Drapkina (Кардиоваскулярная терапия и профилактика)
Aim. To assess the changes of body mass index (BMI) and diet in patients with class 1 obesity receiving low-frequency transcutaneous vagal nerve stimulation (tVNS).Material and methods. This randomized, placebo-controlled study included 88 patients with class 1 obesity and no noncommunicable diseases. The subjects were divided into 2 comparable groups using a random number generator. The patients underwent a comprehensive nutritional analysis using a 24-hour dietary recall and BMI assessment at visit 1 and at a control visit after 6 months of stimulation. Six patients dropped out during the study, and 82 subjects were analyzed over a follow-up period.Results. In the tVNS group, a significant decrease in BMI was found after 6 months — 33,1 vs 31,6 kg/m2 (p<0,001) compared to placebo — 31,5 vs 31,8 kg/m2 (p<0,819). There was a decrease in the average daily value in the tVNS group after 6 months — 2536,0 vs 1854,0 g/day (p<0,001). The median indicators of total fat, cholesterol and carbohydrates significantly decreased in the tVNS group — 100,8 vs 85,9 g/day (p=0,009), 322,4 vs 195,5 mg/day (p=0,005), 274,4 vs 213,5 mg/day (p=0,001), respectively, compared to placebo — 116,2 vs 91,2 g/day (p=0,791), 357,0 vs 249,5 mg/day (p=0,110), 250,8 vs 196,3 mg/day (p=0,129), respectively.Conclusion. For the first time, against the background of tVNS, a decrease in BMI, daily calorie intake and consumption of total fat, dietary cholesterol and total carbohydrates was revealed in individuals with class 1 obesity.